2019
DOI: 10.3390/genes10100774
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Whole-Plastome Sequence between the Bonin Islands Endemic Rubus boninensis and Its Close Relative, Rubus trifidus (Rosaceae), in the Southern Korean Peninsula

Abstract: Rubus boninensis is a rare endemic species found on the Bonin Islands with a very restricted distribution. It is morphologically most closely related to Rubus trifidus, occurring widely in the southern Korean peninsula and Japan. This species pair provides a good example of anagenetic speciation on an oceanic island in the northwestern Pacific Ocean—R. trifidus as a continental progenitor and R. boninensis as an insular derivative species. In this study, we firstly characterized the complete plastome of R. bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
10
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 52 publications
5
10
1
Order By: Relevance
“…In addition, the non-coding regions were found to be more divergent and variable than the coding regions. As expected, these findings are consistent with the patterns observed in common angiosperms [ 44 , 47 , 49 , 60 , 61 ]. These six plastomes are highly conserved despite differences in estimated divergence times in the Late Cretaceous period, with the crown ages of Rosoideae and Amygdaloideae being estimated to be 75.78 million and 90.18 million years, respectively [ 10 ].…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, the non-coding regions were found to be more divergent and variable than the coding regions. As expected, these findings are consistent with the patterns observed in common angiosperms [ 44 , 47 , 49 , 60 , 61 ]. These six plastomes are highly conserved despite differences in estimated divergence times in the Late Cretaceous period, with the crown ages of Rosoideae and Amygdaloideae being estimated to be 75.78 million and 90.18 million years, respectively [ 10 ].…”
Section: Resultssupporting
confidence: 91%
“…The relative synonymous codon usage (RSCU) value was also similar to that in R. takesimensis . Consistent with the patterns detected in Rubus [ 60 ] and other angiosperms [ 61 ] and algal lineages [ 62 ], we found that codon usage in the P. dickinsii var. glabrata and S. insularis plastomes is biased toward a high RSCU value of U and A at the third codon position.…”
Section: Resultssupporting
confidence: 90%
“…The eight plastomes of Taiwanese endemic Rubus contained 131 genes: 84 protein-coding, eight ribosomal RNA, and 37 transfer RNA genes. Compared with previously reported GC content of Rubus plastomes (37.1%) 35 39 , the overall GC content ranged from 37.0% ( R . glandulosopunctatus, R. rubroangustifolius, and R. taiwanicolus ) to 37.3% ( R. incanus, R. parviaralifolius, and R .…”
Section: Resultscontrasting
confidence: 75%
“…In addition, despite their representations from two subgenera ( Idaeobatus and Malachobatus ), the plastomes are highly conserved, with no structural variations or content rearrangements. Interestingly, the highly conserved group II intron of atpF gene was lost in all eight plastomes regardless of their subgeneric assignments, as we demonstrated previously in the case of R. boninensis, R. crataegifolius, R. takesimensis and R. trifidus 35 , 39 . Within the major lineages of the family Rosaceae 45 , we found the complete atpF gene in members of the newly circumscribed subfamily Amygdaloideae, such as Prunus (KP732472), Pyrus (HG737342, AP012207), and Malus (NC040170, NC031163).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation